2022
DOI: 10.1590/1678-4324-2022220145
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Response of Seeds of Crotalaria spectabilis under Drought and Heat Stress

Abstract: This study evaluate the effect of drought and heat stress on the quality of C. spectabilis seeds. A completely randomized design in a 4×4 factorial scheme, referring to four osmotic potentials based on Polyethylene glycol (PEG 6000 = 0.0, -0.2, -0.4 and -0.8 MPa) and four temperatures (25, 30 and 35 ºC constant and alternating between 25-35 ºC), with four replications of 50 seeds per plot was used. The germination percentage, first count germination, germination speed index, average germination time, average g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…However, the reduction of the osmotic potential negatively affects the mobilization of stored reserves, the structural organization of proteins, the activity of phytohormones, in addition to increasing oxidative stress, due to the toxic effect of ions in the solution (Ibrahim, 2016). Sunflower (Helianthus annuus L.) and Crotalaria spectabilis Roth seeds under water stress (Carneiro et al, 2011;Nóbrega et al, 2022) showed a reduction in germination and vigor with osmotic potentials below -0.20 MPa; however, the use of solutions with potential above -0.20 Mpa did not affect germination, which remained around 90%.…”
Section: Resultsmentioning
confidence: 99%
“…However, the reduction of the osmotic potential negatively affects the mobilization of stored reserves, the structural organization of proteins, the activity of phytohormones, in addition to increasing oxidative stress, due to the toxic effect of ions in the solution (Ibrahim, 2016). Sunflower (Helianthus annuus L.) and Crotalaria spectabilis Roth seeds under water stress (Carneiro et al, 2011;Nóbrega et al, 2022) showed a reduction in germination and vigor with osmotic potentials below -0.20 MPa; however, the use of solutions with potential above -0.20 Mpa did not affect germination, which remained around 90%.…”
Section: Resultsmentioning
confidence: 99%
“…Negative effect of water deficit on germination was also observed on the vigor of C. pyramidale seeds, with decreases of 63 and 83% in the FGC and GSI values at an osmotic potential of -1.2 MPa, accentuating the effect of water stress on seed quality. Reduced water availability causes changes in germination metabolism, compromising pre-germination metabolic processes, delaying the development of the embryonic axis (Nóbrega et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…DÉFICIT HÍDRICO (Ferreira et al, 2022). It is a species adapted to the conditions of the semi-arid Northeast of Brazil, a region characterized by high temperatures and irregular rainfall, which can compromise the germination and initial establishment of this species, since they are the most sensitive stages to stress conditions (Nóbrega et al, 2022).…”
Section: Osmocondicionamento De Sementes Com áCido Salicílico Na Indu...mentioning
confidence: 99%
“…Okcu [57] in the study investigating the effects of different salt concentrations on germination and seedling development in forage cowpeas at doses of 0-270 mM, stated that the germination rate varied between 30.20 and 98.60%, and the highest value was determined in the control group, while the highest average germination time varied between 2.00 and 3.36 days, and reported that germination times were determined at concentrations of 210, 240, and 270 mM. Nóbrega et al [58] have found a shoot length of 7.46 cm and a root length between 2.68 and 3.14 cm without any implementation. Ates and Tekeli [48] determined the germination rate on day seven at 100,00%, 100.00%, and 7.17% at 0 mM, 100 mM, and 150 mM in three different Persian clover lines, respectively.…”
Section: Discussionmentioning
confidence: 99%